Representações sobre o processo de ensino-aprendizagem de língua inglesa dos alunos da 5ª a 8ª séries de uma escola pública do Estado de São Paulo - Ricci, Andréa (2007)
This research aims at identifying the social representations of the students from the 5th and 8th grades about the teaching and learning process of the English language in a public school as well as the similarities and/or differences between these representations, in order to establish a more realistic teaching and learning process of the English language, with clear and possible objectives to be achieved and associated with the social function of the language, that is, with the function of this foreign language in the construction of the citizenship and as part of his global education. The foundations on which this study is based are the concept of social representation proposed by Moscovici (2003), corroborated by Wagner (1995) and Jodelet (1984). The Parâmetros Curriculares Nacionais Língua Estrangeira (Brasil, 1998), the models of language description of Graddol (1994), besides the concepts of teaching and learning process by Mizukami (1986), Rego (1995), Giusta (2003) and Willians & Burden (1997). This research was conducted in a public school in the interior of São Paulo State where the teacher-researcher works, with 10 of her students, five from the 5th grade and five from the 8th grade. The data was collected in the second semester of 2005 by questionnaires and an interview. The results indicate that once these representations are identified it is possible to know the students´ reality better and redirect the English lessons to the education of citizens capable of taking part in the construction of a better society, conscious of their rights and duties, as well as to the job market and to the world changes